In-Store Marketing Strategies towards Customer Attitude to Private Label Brands using Cue Utilization Theory - Ronaldo Yolanda Putra; Syifa Nurul Fadillah (The Winners, 2022)
The research aimed to find out instore marketing strategies that can influence consumer attitudes towards private label brands based on “cue utilization theory”. The research belonged to the category of explanatory research since it uses primary data with the population of consumers who have shopped for private label products in Hypermart Tanjungpinang, and sample as many as 174 respondents with convenience sampling techniques. The analysis approach uses partial least square-structural equation modeling (PLS-SEM). The results show that private label marketing has a positive and significant effect on private label attitudes; private label marketing and store environment positively and  significantly influence private label attitudes through the mediation role of perceived quality variants; product related attributes have a positive and significant influence on private label attitudes; the national brand promotion attitudes  does not moderate the relationship between private label marketing and perceived quality variants on private label  attitude; and price consciousness does not moderate the relationship between private label marketing and perceived quality variants on private label attitudes.